PF-9 Seroprevalence of H5N1 Avian Influenza Subtype in Backyard Duck at Kampung Unggas Teruwai on Central Lombok District - Yumi Sartika; Andreayani Attamimi; Siti Rahmawati; . Kholik (Hemera Zoa, 2018)
Avian influenza is one of the zoonotic diseases. Since 2003, H5N1 Avian Influenza subtype was circulated in Indonesia, affecting both intensively farmed birds as well as backyard chickens [1]. Duck is the reservoir of avian influenza viruses. Backyard duck may play a role in the maintenance of H5N1 avian influenza subtype.Kampung Unggas that located in Teruwai Village on Central Lombok District is one of the economic centers of a farmer on Lombok Islands and The Avian Influenza Virus is still the major problems in this village. H5 Avian Influenza was detected in quail at Central Lombok district in 2014 [2]. In 2017, Sentinel chicken were positive antibodies for H5 AIV with Geometric Mean Titer (GMT) = 24,29 at Kampus Unggas Teruwai [3].To know seroprevalence of H5N1 Avian Influenza subtype in duck as a reservoir and to understand the current situation of H5N1 Avian Influenza virus circulation in Kampung unggas, we conducted serosurvey study from Mei to April 2018 of backyard duck that lives together with chickens in Kampung Unggas.